2020
DOI: 10.1007/s11242-020-01496-9
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Relative Permeabilities Under Gas Liberation or Condensate Precipitation in Porous Medium

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 48 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…These values agree with the values of critical gas saturation for North Sea cores found in the literature. • Finally, it has been shown that by using the model developed in our previous work (Al-Masri and Shapiro, 2020), it may be possible to use the results from the proposed experiment to predict the whole relative permeability curves for both the oil and gas phases. This conclusion needs further experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…These values agree with the values of critical gas saturation for North Sea cores found in the literature. • Finally, it has been shown that by using the model developed in our previous work (Al-Masri and Shapiro, 2020), it may be possible to use the results from the proposed experiment to predict the whole relative permeability curves for both the oil and gas phases. This conclusion needs further experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model in [16] expresses the relative permeabilities [8] in terms of microscopic characteristics of the porous medium and validates the model at the core scale. In the present work, we apply for the first time the relative permeabilities [8,16] at the reservoir scale.…”
Section: Introductionmentioning
confidence: 76%
“…A mathematical model in [16] expresses the relative permeabilities [8] in terms of microscopic characteristics of the porous medium and validates the model at the core scale. In the present work, we apply for the first time the relative permeabilities [8,16] at the reservoir scale. The goal is to verify, whether the new permeabilities may be applied for history matching and recovery forecast on a large scale, and, whether they may explain the observed discrepancies between the oil production between the different Valdemar wells.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations